Perlindungan Hukum Terhadap Anak Korban Kekerasan Seksual Pada Konflik Bersenjata Non-Internasional - Waas, Armelia Febriyanty (Fakultas Hukum Universitas Pattimura, 2024)
Introductioan: Cases of sexual violence against children in non-international armed conflicts have long been recognized as deliberate and systematic violence. After that, legal protection against violence becomes very important to provide not only in times of peace but also in times of conflict. Sexual violence committed in non-international armed conflicts is categorized as a war crime and a crime against humanity, especially for minors as victims. So it is necessary to implement legal protection for children as victims of sexual violence in non-international armed conflicts.Purposes of the Research: Examining and analyzing the legal protection provided to children as victims of sexual violence in non-international armed conflicts.Methods of the Research: The research was conducted through normative legal research with a legal approach to examine and analyze regulations relating to the legal protection of children as victims of sexual violence in non-international armed conflicts.Results of the Research: There are regulations relating to the protection of victims of sexual violence, especially children, committed intentionally by combatants in armed conflict. Legal protection, especially in non-international armed conflicts, is also part of the State's responsibility in resolving this case. So that there is implementation of rules related to the protection of human rights in armed conflict with all assistance from international organizations based on international humanitarian law which has provided legal protection for victims of sexual violence.